Health and prosperity efficient health systems for thriving nations in the 21st century - Murtin, Fabrice (Palgrave pivot, 2016)
"Murtin examines the long-term causes of health improvements over the last two centuries. Focusing on the relative importance of income and education, Murtin finds that education alone accounts for the bulk of health improvements since 1870, and explains the strong correlation between longevity and income, which is highly correlated with education. Conversely, the book shows that progress in longevity has had dramatic consequences on societies, as it reduced fertility, triggered the spread of education, spurred economic growth, and improved 'prosperity' in a way that is comparable to the long-term rise in income. Health and Prosperity sheds light on the real cost of health systems in the 21st century"-- Provided by publisher.